Análise global da diversidade de microorganismo importantes para a fermentação nas usinas de álcool: uma abordagem utilizando metagenômica - Lima, Larissa Barbosa de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Brazil is the second world's largest producer of ethanol and, to keep this production, there is a huge concern by this industry regarding bacterial contamination. Due to the non-sterile process conditions, bacteria present in the raw material that fuels the production of ethanol are common contaminants. To combat them, factories uses randomly antimicrobial, a practice that increases the price of alcohol in addition to generating resistant bacteria and leave waste on the environment. This said, the identification of contaminants in different industrial environments is necessary, as well as the search for new technologies for the control of contaminants from alcoholic fermentation. In this project, it will be shown that the molecular technique of using metagenomic 16S, applied to samples of content of the tanks of the 2013 harvest, corroborates earlier studies and shows it as a rapid and efficient method for identifying contaminating microorganisms. Our results obtained using next generation sequencing in high-throughput platform confirm the predominance of Lactobacillus spp in fermentation, and the presence of other contaminants not previously described as Rubrobacter xylanophilus, Cloacibacterium normanense and Diaphorobacter nitroreducens, which enables the development of personalized treatment

O Brasil é segundo maior produtor mundial de etanol e para manter seu rendimento há uma grande preocupação por parte das usinas quanto à contaminação bacteriana. Bactérias presentes na matéria-prima que alimenta a produção de etanol são frequentes contaminantes, por conta das condições não estéreis do processo. Para combatê-las as usinas utilizam antimicrobianos aleatoriamente, prática esta que encarece o preço do álcool além de gerar bactérias resistentes e deixar resíduos no ambiente. Deste modo, a identificação dos contaminantes em ambientes industriais distintos, se faz necessária, bem como a busca de novas tecnologias para o controle de contaminantes da fermentação alcoólica. Aqui, nós mostramos que a técnica molecular de metagenômica utilizando a região 16S, aplicada a amostras do conteúdo de dornas da safra de 2013, corrobora estudos anteriores e se mostra rápida e eficiente para a identificação de micro-organismos contaminantes. Nossos resultados obtidos através de sequenciamento de segunda geração em plataforma de alto rendimento confirmam a predominância de Lactobacillus spp na fermentação, além da presença de outros contaminantes não descritos anteriormente como: Rubrobacter xylanophilus, Cloacibacterium normanense e Diaphorobacter nitroreducens, o que permite a elaboração de um tratamento personalizado
Keywords: Álcool - Combustível - Indústria; Álcool como combustível - Contaminação; Lactobacilo; Metagenomica; Fermentação; Etanol; Contaminação; Alcohol as fuel